Menjelajahi Komposisi Musik Instrumental Kontemporer: Teknik dan Tren di Era Modern - Robby Ferdian; Hengki Armez Hidayat; Irdhan Epria Darma Putra; Olan Yogha Pratama (SENDRATASIK UNP, 2023)
Contemporary instrumental music has developed rapidly in recent decades, creating unique sounds and attracting the attention of many listeners. This article aims to explore the techniques and trends in contemporary instrumental music composition in the modern era. The methods used in this research are data analysis and literature review, which include case studies of several prominent instrumental music composers, as well as a review of the latest techniques in contemporary instrumental music composition. The results of this research show that in contemporary instrumental music composition, composers use various techniques to create more dynamic and complex music. Some commonly used techniques are the use of complex harmonies, unusual musical instruments, and modern technology to create innovative sound effects. Trends in contemporary instrumental music composition also continue to change over time, ranging from the fusion of different music genres to the use of AI technology and real-time music applications for sound design. In conclusion, this article provides an overview of the techniques and trends in contemporary instrumental music composition in the modern era. It is hoped that this will provide insights and inspiration for composers, music enthusiasts, and stakeholders in the music industry to continue to develop and create innovative and interesting music in the future.